Towards a new concept of leadership - Labourdette, Sergio; Scaricabarozzi, Rossana (2010)
In the present work we have posited some necessary guidelines to reformulate an essential pillar of leadership: the relationship group-leader. The set of enunciations that are developed are meant to establish the basic principles of the theoretical interpretation of this essential phenomenon of social life. In most works dealing with leadership we usually find that texts are centred on the leader. However, the process possesses another member of even greater importance embodied in the social group that forms around him or her. Thus, social actors need to reach a higher degree of sociability and to express, amongst other things, needs and goals, and they look for them openly in a chosen representative. And he or she, in turn, must fulfil the expectations of the group. In other words, the asymmetry of said relationship is inverted. Moreover, at the leader's end, we must discern between the person and the 'character'. This is how the particular game of leadership unfolds. The resulting construct accounts for the construction of a significant social feat.
Keywords: Leadership; Group; Leader; Character; Individual; Identification; Social construction; Liderazgo